PENULISAN NOTASI ANGKA MENGGUNAKAN PARNUMATION 3.0 SEBAGAI UPAYA PEMANFAATAN TEKNOLOGI PADA ERA DISRUPSI BAGI GURU SENI BUDAYA DI KABUPATEN SOLOK - Fajry Sub'haan Syah Sinaga; Emah Winangsit (Universitas Negeri Padang, 2019)
Based on research (S. S. Sinaga, 2010) a music teacher must be able to transcribe a music notation in the music learning process. This article provides an introduction on how to write numbered music notation using Parnumation 3.0 as an effort to utilize technology in the digital age. This study uses descriptive analytics with data collection methods consisting of observation and literacy studies that support the steps for submitting number notations using parnumation 3.0. The research proves that the use of parnumation 3.0 provides a compromise on notation